Fonts per a l'estudi de la fraseologia catalana - Calatayud, Josep V.; Luna, Xavier (Caplletra. Revista Internacional de Filologia, 1995)
This article has a practical and orientative purpose: through the Catalan lexicographical production, it introduces a list of collections of idioms classified according to whether they incorporate with more or less intensity the reality of the idioms, in order to facilitate further investigations.